Full life cycle analysis of usability in IoT systems - Du Plessis, E. (North-West University (South Africa), 2020)
Usability in IoT systems has not been clearly defined, and even more so over a system full life cycle. The concept of usabililty over a full life cycle is not commonly encountered, and a research question arose as to its definition. A comprehensive literature study validated the limited definition of usability in IoT system life cycle phases. Literature also supported the observation that usability has its main focus on end-users during the system's operational and maintenance phase. A usability baseline is thus needed to define usability over all system life cycle phases and must include all system users and stakeholders from a system perspective. Firstly, a definition for general IoT systems was derived to form a foundation for the usability framework that includes all system life cycle phases, users, and stakeholders. Secondly, the life cycle usability framework was developed using Nielsen's usability heuristics as a baseline from which to develop a set of generalised usability heuristics that can be applied to IoT systems, as opposed to Nielsen's end-product usability view. The framework was validated by applying the life cycle heuristics to general usability issues in IoT systems as obtained from literature, a peer-reviewed IEEE conference article that commended the work, and by application of the life cycle heuristics to the development and successful deployment of a centre pivot irrigation system (CPIS). The life cycle usability heuristics were found to address the general usability issues, as well as improving the perspective and definition of usability over the life cycle of the CPIS. Many of the life cycle usability heuristics were found to be addressed by systems engineering functions, with model-based systems engineering adding notable value. The value of systems engineering showed that proper application of systems engineering processes and methods, augmented with effective contextualisation, constructivism, complexity reduction, and effective communication form a valid full life cycle usability baseline for IoT systems.
MEng (Computer and Electronic Engineering), North-West University, Potchefstroom Campus
Keywords: Usability; system; full life cycle; heuristics; centre pivot irrigation system